A Description of Preschool Parents Perceptions of Kindergarten Readiness - Dinar, Eqlima (2015)
Children as young as three are being assessed whether they are ready or not for kindergarten by examining their academic skills which have raised parents’ concerns about their children’s ability to be successful in formal schooling. Parents are a child’s first teacher and their beliefs about readiness affect the kind of experiences and materials which they provide for their children and knowing their perceptions could benefit teachers, schools and legislators in this region for improving the quality of early childhood education. Kindergarten readiness is a complex construct that involves multiple dimensions of children development. This descriptive survey study was conducted to describe preschool parents perceptions about the skills that they believe are important for their child to be ready for kindergarten. By utilizing the National Education Goal Panel framework of readiness, an online questionnaire was constructed and distributed to a convenient sample of 76 parents of 3 to 4 years old children who are enrolled in the United Arab Emirates preschools. Parents reported that Social and Emotional domains were most crucial to children’s success in kindergarten yet they focused on academic instruction when engaging in activities with their children. The findings of the study can be utilized to better inform parents about the skills that are crucial for readiness, help teachers in designing better instructional experiences and aid legislators in planning and implanting policies that could improve the quality of early childhood education in the country. Further research is still required on this topic that can be on larger scale so that it would generalizable to a bigger population.